Municipal Awareness and Citizen Satisfaction: The Case of the Northern Borders in Saudi Arabia - Almarshad, Sultan O. (International Review of Management and Marketing, 2015)
The literature suggests a strong relationship between municipal awareness and citizen satisfaction. This study aims at examining the determinants of municipal awareness, and their impacts on citizen satisfaction. The model of this study was validated in the context of the kingdom of Saudi Arabia with 250 inhabitants in the region of Northern Borders. The study data is collected and processed using exploratory and confirmatory analysis, based on survey methods and structural equations. The results revealed a positive association between municipal awareness and citizen satisfaction. Overall, findings suggest that knowledge, discussion, participation and learning about municipal achievements, as indicators of municipal awareness, affect citizen satisfaction with the quality of the municipal services. Keywords: Municipal awareness; citizen satisfaction; local development. JEL Classifications: H72; O18